Development of a new grip for use with a long cane for visually impaired children. (August 2019) - Shimizu, Junichi; Yoshioka, Manabu; Yonetsu, Ryo; Nakao, Hiroki; Kizaki, Hideomi
Statement of context: A new grip part for the long cane used by visually impaired children was developed and the effect of this grip, using the muscle activity of the upper limbs, investigated. Critical reflection on practice: When using a long cane with this newly designed grip, the upper limb manipulating the cane showed less muscle activity than when using the conventional grip part. Implications for practice: Since long canes with the new grips require less muscle activity in their operation, they are popular, making it possible to encourage their use from the lower grade of elementary school.